2014
DOI: 10.1002/cne.23549
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of neurotransmitter receptors and zinc in the pigeon (Columba livia) hippocampal formation: A basis for further comparison with the mammalian hippocampus

Abstract: The avian hippocampal formation (HF) and mammalian hippocampus share a similar functional role in spatial cognition, but the underlying neuronal mechanisms allowing the functional similarity are incompletely understood. To understand better the organization of the avian HF and its transmitter receptors, we analyzed binding site densities for glutamatergic AMPA, NMDA, and kainate receptors; GABAA receptors; muscarinic M1 , M2 and nicotinic (nACh) acetylcholine receptors; noradrenergic α1 and α2 receptors; serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
116
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(122 citation statements)
references
References 109 publications
6
116
0
Order By: Relevance
“…One important issue regarding the comparison of the HF between birds, reptiles, and mammals is the recurrent assumption that the cytoarchitecture of this region in birds is different to that in reptiles and mammals because it shows a nonlaminar organization [for example, discussed by Herold et al, 2014]. In contrast to this view, developmental studies have shown that this structure is also formed according to a layered cytoarchitectonic pattern [Redies et al, 2001].…”
Section: Hippocampal Subdivisions In Chicken and Reptiles Based On Gementioning
confidence: 85%
See 4 more Smart Citations
“…One important issue regarding the comparison of the HF between birds, reptiles, and mammals is the recurrent assumption that the cytoarchitecture of this region in birds is different to that in reptiles and mammals because it shows a nonlaminar organization [for example, discussed by Herold et al, 2014]. In contrast to this view, developmental studies have shown that this structure is also formed according to a layered cytoarchitectonic pattern [Redies et al, 2001].…”
Section: Hippocampal Subdivisions In Chicken and Reptiles Based On Gementioning
confidence: 85%
“…The latter field was previously suggested to be a caudolateral extension of the APH (and was accordingly called APHcl) based on its cytoarchitecture and cadherin expression profile [Redies et al, 2001]. In adult pigeons, all of these areas, including the hippocampus and all APH, show moderate to strong zinc expression with differences between different layers, resembling hippocampal projections in mammals [Herold et al, 2014; note that zinc ions are also present in many corticocortical and other palliopallial glutamatergic projections, but they show a remarkably high concentration in the hippocampal mossy fiber system; Paoletti et al, 2009]. As in mammals, the density of zinc-positive terminals in the avian hippocampal complex correlates well with that of NMDA glutamate synapses [Herold et al, 2014].…”
Section: Hippocampal Complex Of Chicken and Lizard Based On Genoarchimentioning
confidence: 99%
See 3 more Smart Citations